Vexing, Veiled, and Inequitable: Social Distancing and the "Rights" Divide in the Age of COVID-19. Issue 7 (2nd July 2020) - Fairchild, Amy; Gostin, Lawrence; Bayer, Ronald
Abstract: Although unprecedented in scope and beyond all our life experiences, sweeping social distancing measures are not without historical precedent. Historically, racism, stigma, and discrimination resulted in grossly inequitable application of disease containment measures. But history also provides examples in which broad measures enjoyed remarkable public support. When it comes to COVID-19, blame and division continue to shape containment responses. But the COVID-19 pandemic also resonates with moments in which there was broad social support for containment precisely because lockdowns or stay at home orders are, on the surface, remarkably equitable. Yet even in a context in which a majority of Americans support social distancing, small but coordinated conservative groups are challenging social distancing as a matter of individual rights. In sharp contrast, vulnerable populations, who bear the heaviest burden of disease, have claimed a right to social distancing as a matter of protection.